2021
DOI: 10.1111/jpy.13170
|View full text |Cite
|
Sign up to set email alerts
|

High Iron Requirements for Growth in the Nuisance Alga Gonyostomum semen (Raphidophyceae)

Abstract: The bloom‐forming freshwater alga Gonyostomum semen is associated with acidic, mesotrophic brown water lakes in boreal regions. However, researchers have been unable to conclusively link G. semen abundance and bloom formation to typical brown water lake traits, that is, high water color and DOC (dissolved organic carbon) concentrations. Iron is a main driver of water color in boreal lakes, and a recent study of lake monitoring data indicated a connection between lakes with high G. semen abundance and iron conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…Similarly, some other studies have shown a higher growth rate with increased iron levels, e.g. the green alga C. vulgaris and flagellate Gonyostomum semen cultures grew better at high iron levels ( Liu et al., 2008 ; Munzner et al., 2021 ). By contrast, the eustigmatophyte Nannochloropsis salina , haptophyte Pleurochrysis carterae , and Chlamydomonas sp.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similarly, some other studies have shown a higher growth rate with increased iron levels, e.g. the green alga C. vulgaris and flagellate Gonyostomum semen cultures grew better at high iron levels ( Liu et al., 2008 ; Munzner et al., 2021 ). By contrast, the eustigmatophyte Nannochloropsis salina , haptophyte Pleurochrysis carterae , and Chlamydomonas sp.…”
Section: Discussionsupporting
confidence: 60%
“…By contrast, the eustigmatophyte Nannochloropsis salina , haptophyte Pleurochrysis carterae , and Chlamydomonas sp. showed their highest growth rate at low iron levels ( Tiamiyu, 2011 ; Munzner et al., 2021 ). Furthermore, Weng et al., 2008 found that iron deprivation could lead to slower growth rate in Cryptomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ]). In the laboratory, we have shown that G. semen growth requires high Fe [ 63 ] and field observations connect Fe and presence of G. semen blooms [ 64 ]. Moreover, in Gollnisch et al .…”
Section: Discussionmentioning
confidence: 99%
“…Individual cells were isolated manually, washed three times, and transferred to separate wells of a 48-well tissue culture plate. For the freshwater strains the wells contained 50% sterile-filtered lake water and the remainder artificial MWC medium with a selenium (Se) amendment (see 46 ). Cultures were grown at 4 °C in at 12:12 LD cycle at 50 µmol photons m -2 s -1 .…”
Section: Sampling and Isolation Of Dinoflagellate Strainsmentioning
confidence: 99%